Robust Porcine GFR Measurement with Radiotracers and Only Late Blood Samples - Lars Jødal; Juan Ignacio Brignone; Pui-Ki Chan Ladefoged; Lars Lund; Trine Borup Andersen (Biologics, 2023)
(1) Pigs are physiologically very relevant as animal models of human physiology. Radiotracer methods for porcine GFR (glomerular filtration rate) determination exist but require full-curve blood sampling or the application of correction formulas, which vary among studies. (2) We used porcine GFR data (40 datapoints from 20 juvenile pigs) for which the GFR was measured as the plasma clearance of [99mTc]Tc-DTPA. The reference clearance (Cl, GFR; range 41–85 mL/min) was measured from the full curve under the data. For simpler determination, an approximate clearance, Cl1, was based on the last five blood samples (acquired 120–240 min post injection). (3) The following formula for the GFR was developed: Cl = 1.27 · (Cl1)0.92. The spread (SD) was within 4% of the reference GFR. A comparison with the literature data showed that our correction formula was robust in pigs of various breeds, sizes up to approximately 200 kg, and GFRs up to approximately 400 mL/min, with a spread of up to 8%. The formula was also applicable for iohexol as the tracer. (4) A formula was developed that allows porcine GFR to be measured using only 4–5 late blood samples. This new formula can be applied across a wide range of swine breeds, animal sizes, and GFR ranges, allowing for robust determination of the GFR in pigs without full-curve blood sampling and without urine collection.